A layerwise model for soft core sandwich panels - R. Moreira (2004)
The application of high damping materials, like high loss factor viscoelastic materials, in the core of sandwich plates can improve their dynamic response and reduce fatigue failure. However, the numerical simulation of the effects of this kind of damping treatment demands a cumbersome computational work, specially during the spatial modelling task of the layered structure. In this work, a layerwise model is developed and applied in the analysis of sandwich plates with thin viscoelastic cores, comparing the results achieved with those obtained with the usual modelling approach using a layered combination of standard plate and solid finite elements. The proposed model can correctly describe the high shear pattern developed inside the thin viscoelastic core, providing results similar to those obtained with the layered models.